Recollection of Agapetes miranda Airy Shaw (Ericaceae) from Arunachal Pradesh, lndia - Panda, S. (Rheedea, 2007)
Agapetes miranda Airy Shaw was recollected from Arunachal Pradesh after a gap of 69 years. The species is described and illustrated, and its fruit is described for the first time.